WILD EDIBLE PLANTS IN ENHANCING POST-DISASTER FOOD SECURITY, ORMOC CITY, PHILIPPINES - Patricia Anne Nazareno; Prof Ricardo Bagarinao; Inocencio Jr. Buot; Cindy Ochavillo (SEAMEO BIOTROP, 2025)
Article Highlights:- Wild edible plants (WEPs) in Ormoc City, Philippines, serve as critical food sources during disasters, offering essential nutrients and aiding food security.- Melastoma malabathricum is rich in calcium, magnesium, and manganese, while Diplazium esculentum provides high levels of iron, copper, and zinc.- Wild fruits like Melastoma malabathricum, Annona montana, and Rubus fraxinifolius contribute significant Vitamin C to the local diet.- These plants not only provide sustenance but also offer medicinal benefits, emphasizing the need for further research, conservation, and sustainable use. ABSTRACTWild Edible Plants (WEPs) are a valuable resource for communities facing food insecurity, and their nutritional profiles can provide essential dietary needs, especially in disaster-prone regions like the Philippines. This paper explores the nutritional value of wild edible plants (WEPs) in Ormoc City, Leyte, Philippines, with a particular focus on their role in addressing food security issues during natural disasters. The research included surveying the WEPs used by the local community in Ormoc City and analyzing these plants' nutrient and mineral composition. The study's key findings included identifying 15 plant species from 13 families. Melastoma malabathricum showed the highest Ca, Mg and Mn content; while Diplazium esculentum leaves had the highest iron, copper and zinc content. Furthermore, relatively high vitamin C content was found in wild fruits M. malabathricum, Annona montana, and Rubus fraxinifolius. The plants analyzed were rich in essential nutrients, including minerals (Ca, Na, Mg, Mn, Fe, Cu and Zn), crude fiber and vitamin C. The different plants excelled in different nutritional aspects, suggesting a diverse dietary potential. These plants play a crucial role in the local community, providing not only sustenance but also medicinal applications. Further research and conservation efforts should be encouraged to harness the nutritional and economic potential of these plants while ensuring their sustainable utilization and preservation.